Developing a Crisis Management System for Local International Exchanges: Insights for Sports Organizations in the Internet+ Era - Xintong Yu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In the era of globalization and digital transformation, international relations have evolved into a multi-level framework encompassing supranational, national, and local government interactions. Since the 1970s, local governments have increasingly engaged in foreign affairs, influencing the formulation and execution of national foreign policies. Their role has become critical as economic and trade relations between regions and foreign entities expand, with local governments' decisions significantly impacting international trade, investment trends, and global partnerships. Harbin, China's northernmost economically advanced city, exemplifies this dynamic with its extensive exchanges with European countries. Using Harbin's communication with European nations as a case study, this research analyzes the construction of a crisis management system for local and international exchanges in the Internet+ era. The study highlights the importance of integrating digital technologies to address challenges in real time communication, cultural exchanges, and strategic collaboration. These findings have valuable implications for sports organizations, particularly those involved in international competitions, exchanges, and partnerships. Establishing robust crisis management systems ensures effective communication, mitigates risks, and fosters positive relationships across borders. By leveraging digital tools and fostering strategic coordination, sports organizations can enhance their adaptability and resilience in the increasingly interconnected global environment.